Research trends in the field of the gut-brain interaction: Functional dyspepsia in the spotlight – An integrated bibliometric and science mapping approach - Zhang, Tai; Zhang, Beihua; Ma, Xiangxue; Zhang, Jiaqi; Wei, Yuchen; Wang, Fengyun; Tang, Xudong (Frontiers in Neuroscience, 2023)
Objectives: This study aims to perform a bibliometric analysis of functional dyspepsia (FD), which includes visualizing bibliographic information, in order to identify prevailing study themes, topics of interest, contributing journals, countries, institutions, and authors as well as co-citation patterns. Methods: Based on a search of the Web of Science database, publications addressing FD were retrieved from 2006 onwards. With the assistance of CiteSpace and VOSviewer software, publication information, co-citations, authors, affiliated institutions and countries as well as author keywords were visualized and presented. Results: A search of the database retrieved 2,715 documents, with a surge in publications since 2018. The USA, China, and Japan provided the majority of contributions. In terms of institution, Mayo Clin, Univ Newcastle, and Katholieke Univ Leuven were found to be the prolific institutions. The majority of publications relating to the topic were published by Asian authors, but collaboration clusters were largely organized by European researchers. In Asia, research has until now been almost exclusively focused on complementary and alternative medicine and has been limited to a few centers in the East Asian region. Seven thematic clusters emerged (first cluster: pathophysiological mechanisms; second cluster: Helicobacter pylori infection; third cluster: overlapping syndromes; fourth cluster: gut microbiota; fifth cluster: gastrointestinal motility; sixth cluster: diagnosis; and seventh cluster: gastroparesis). Eosinophil-mast cell axis, gut microbiota, mental disorders, and acupuncture are future areas of research for FD. Conclusions: In the current study, we provided bibliometrics-based overviews of relevant literature to researchers from different backgrounds and healthcare professionals to provide an in-depth overview of major trends in FD research.